Application of Augmented Reality (AR) In Vocational Education: A Systematic Literature Review - Siddiq Darmawan; Mumu Komaro (VANOS Journal of Mechanical Engineering Education, 2023)
In education, Augmented Reality has been widely used to complement the standard curriculum. This article aims to examine how the application, and impact of the use of AR in Vocational Education. The Systematic Literature Review method is used to identify, study, evaluate, and interpret Augmented Reality in vocational education. Research data were identified by help of the PRISMA 2020 form. Article was collected from Science Direct database. There were 454 articles. After being selected using inclusion and exclusion criteria, the data used were 14 articles. The results of the study reveal that AR is applied in learning as an innovative learning medium, a new approach to learning to improve students' understanding of knowledge, and skills and provide a concrete learning experience. The integration of AR in education has the impact of increasing students' understanding and learning experience, promoting positive attitudes, making the learning process fun and interesting and learning efficiency.